2013
DOI: 10.1182/blood-2013-05-504639
|View full text |Cite
|
Sign up to set email alerts
|

Highly electronegative LDL from patients with ST-elevation myocardial infarction triggers platelet activation and aggregation

Abstract: Key Points• Highly electronegative LDL (L5), which is elevated in patients with STEMI, induces platelet activation and aggregation through LOX-1.• L5 may have a role in promoting thrombogenesis that leads to STEMI.Platelet activation and aggregation underlie acute thrombosis that leads to ST-elevation myocardial infarction (STEMI). L5-highly electronegative low-density lipoprotein (LDL)-is significantly elevated in patients with STEMI. Thus, we examined the role of L5 in thrombogenesis. Plasma LDL from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 47 publications
2
88
0
1
Order By: Relevance
“…Therefore, these findings imply that cellular senescence may mediate endothelial dysfunction and atherogenesis after chronic exposure to a sublethal level of L5. In other studies, we have shown that the concentration of L5 is less than 10 μg/ml in healthy individuals and is 100 μg/ml in patients with acute myocardial infarction (Chan et al., 2013), 20 μg/ml in patients with chronic kidney disease (Chang et al., 2013, 2016), and 100 μg/ml in patients with hypercholesterolemia (Chen et al., 2003). These estimations indicate that the concentration of L5 chosen for our in vitro experiments is the same order of magnitude as the concentration detected in humans, suggesting that our findings may be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these findings imply that cellular senescence may mediate endothelial dysfunction and atherogenesis after chronic exposure to a sublethal level of L5. In other studies, we have shown that the concentration of L5 is less than 10 μg/ml in healthy individuals and is 100 μg/ml in patients with acute myocardial infarction (Chan et al., 2013), 20 μg/ml in patients with chronic kidney disease (Chang et al., 2013, 2016), and 100 μg/ml in patients with hypercholesterolemia (Chen et al., 2003). These estimations indicate that the concentration of L5 chosen for our in vitro experiments is the same order of magnitude as the concentration detected in humans, suggesting that our findings may be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…These estimations indicate that the concentration of L5 chosen for our in vitro experiments is the same order of magnitude as the concentration detected in humans, suggesting that our findings may be clinically relevant. In addition, we previously found that the percentage of L5 in total LDL from patients with myocardial infarction was around 15% (Chan et al., 2013), which is equivalent to an L5 plasma level of approximately 15 mg/dl. If the effects of redistribution and plasma protein binding are omitted, the dosage of L5 used to inject the mice (2 mg kg −1  day −1 ) would presumably reach a plasma concentration of 15 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highly electronegative LDL has been called L5 because it is the fifth, most electronegative subfraction of LDL isolated by using anion-exchange chromatography (23 ). Plasma concentrations of L5 have been shown to be significantly increased in patients with cardiovascular risks, including smokers and patients with diabetes mellitus and hypercholesterolemia (23)(24)(25), and L5 concentrations are increased to an even greater extent in the plasma of patients with ST-elevation myocardial infarction (26 ).…”
Section: Biologic Interactions Of Crp Lox-1 and Atherogenic Ldlmentioning
confidence: 99%
“…[ [21][22][23][24] On the other hand, recent studies showed that LDL(-) had an ability to induce anti-inflammatory cytokines [e.g. interleukin-10 (IL-10)] and counteract inflammatory effects promoted by lipopolysaccharides.…”
Section: Modified Ldl and Atherosclerosismentioning
confidence: 99%